EFEITOS DE INTERVENÇÕES LÚDICAS DIGITAIS EM PACIENTES COM CÃNCER DURANTE A PANDEMIA DA COVID-19 - Sandra Pinto (2022)
PINTO, S. The effects of digital playful interventions in cancer patients during the Covid-19 pandemic. 2022. Dissertação (Mestrado em Enfermagem) - Universidade Federal de Mato Grosso do Sul, Tres Lagos, 2022. Introduction: The Covid-19 pandemic had a direct impact on the emotional state and health-related quality of life of cancer patient in Brazil and around the world. Anxiety, depression and stress experienced by this population related to the fear of contamination, the insecurity about changes in the cancer treatment regimen and the loneliness due to social isolation. In this scenario, recommended emotional stabilization strategies aimed at creating a bond between patient and their health care network professionals and the involvement in activities of distraction and pleasure, helping to reduce acute stress. Digital information and communication technologies facilitate the engagement of patients in health interventions and ensure the establishment of bond in a secure way. Objectives: To evaluate the effects of playful digital interventions on health-related quality of life, depression, anxiety, stress symptoms and social support in cancer patients during the Covid-19 pandemic. Materials and methods: This is an almost-experimental study, based on before and after, which compared the health-related quality of life, depression, anxiety, stress and social support, in three times of a program of digital playful interventions. The research took place between August 2020 and October 2021 in a non-governmental organization in the municipality of Três Lagoas, Mato Grosso do Sul, Brazil. Registered with the organization in 2020 is inclusion criteria, age over 18 and cognitive and clinical conditions to participate, internet access and smartphone and digital literacy. Were excluded Individuals with weaknesses or disabilities that made it impossible to respond to the assessment instruments and participate in interventions, and the discontinuation criterion was to participate in less than 75% of the activities. The final sample consisted of 15 participants. The interventions include the offer of recreational activities: meetings, games, cooking, artistic and corporal expression, weekly, in two stages, lasting four months each. Using a questionnaire developed by the researchers were assessed Sociodemographic and clinical characteristics. The evaluation instruments adopted were the health-related quality of life questionnaire from the European Organization for Research and Treatment of Cancer; Depression, Anxiety and Stress Scale and the Medical Outcome Study Social Support Scale; all adapted and validated for Brazil. Were evaluated patients at the following times: pre, post-intervention1 and post-intervention2. Were used generalized linear models, Friedman and Nemenyi nonparametric tests to verify differences before and after the interventions; considering 5% significance level. Results: The most were female (88.89%), over 50 years old (55.56%), married (44.44%), with less than eight years of study (66, 67%), had breast cancer (66.67%) and was being followed (61.11%). The perception of quality of life improved in post-intervention2 emotional function, than in the pre-intervention period, with statistical significance (p=0.0020). Symptoms of depression (p=0.0106), anxiety (p=0.0002), stress (p=0.0032) and emotional support/positive social interaction (p<0.0001) were better post-intervention1 and post-intervention2, in relation to the pre-intervention time. Conclusion: The digital playful interventions improved the emotional quality of life, depression, anxiety, stress symptoms and emotional support/positive social interaction in cancer patients during the Covid-19 pandemic should be encouraged among this population. Keywords: Oncology nursing. Covid-19. Information Technology. Internet-Based Intervention. Quality of life. Depression. Anxiety. Stress.